Two new species of asterinaceous fungi from Mahabaleshwar, Maharashtra, India - Bhise, Mahendra Ramesh; Patil, C.r.; Salunkhe, C.b. (Phytotaxa, 2014)
The black mildews from Mahabaleshwar are under exploration, among which two species of Asterinaceous fungi occurring on Syzygium spp. (Myrtaceae) are found to be new. These species, viz. Asterina myrtacearum sp. nov. and Lembosia mahabaleshwarensis sp. nov. are reported in this paper. The detail morphological description, colour photographs, line drawings and discussions are provided here for each species.